2021
DOI: 10.3390/jcm10225294
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Gastric Carcinomatosis

Abstract: Diagnosing the absence or presence of peritoneal carcinomatosis in patients with gastric cancer, including its extent and distribution, is an essential step in patients’ therapeutic management. Such diagnosis still remains a radiological challenge. In this article, we review the strengths and weaknesses of the different imaging techniques for the diagnosis of peritoneal carcinomatosis of gastric origin as well as the techniques’ imaging features. We also discuss the assessment of response to treatment and pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Interactively reading the coronal and sagittal planes in addition to the mere axial plane can improve the visualization and localization of PM lesions ( 22 ). Some studies have demonstrated that the additional interpretation of coronal and sagittal planes could improve the detection of lesions on the perihepatic visceral peritoneum and superior parietal peritoneum, which run horizontally ( 12 , 16 , 22 ). The sagittal plane can provide a clear section view of the GCL extending to the transverse colon ( 16 , 22 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interactively reading the coronal and sagittal planes in addition to the mere axial plane can improve the visualization and localization of PM lesions ( 22 ). Some studies have demonstrated that the additional interpretation of coronal and sagittal planes could improve the detection of lesions on the perihepatic visceral peritoneum and superior parietal peritoneum, which run horizontally ( 12 , 16 , 22 ). The sagittal plane can provide a clear section view of the GCL extending to the transverse colon ( 16 , 22 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that the additional interpretation of coronal and sagittal planes could improve the detection of lesions on the perihepatic visceral peritoneum and superior parietal peritoneum, which run horizontally ( 12 , 16 , 22 ). The sagittal plane can provide a clear section view of the GCL extending to the transverse colon ( 16 , 22 , 31 ). One study also described the improvement in sensitivity from 64% in axial planes to 82% in MPR images during the PM diagnosis ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has limited soft tissue contrast, which limits its ability to visualize small peritoneal metastases (PM), especially when adjacent to bowel structures or the mesentery, limiting its sensitivity in detecting lesions and its accuracy in staging PM, as it underestimates the results compared with the surgical Peritoneal Cancer Index (PCI). For this reason, laparoscopy remains the reference for PC staging [ 39 ].…”
Section: Diagnostic Techniquesmentioning
confidence: 99%
“…9 By observing the Brownian movement of water molecules indirectly, diffusion-weighted imaging (DWI) can qualitatively and quantitatively provide morphologic and functional information to distinguish benign from malignant lesions. 10 Although MRI improved the accuracy of TNM staging for AGC, MRI alone is insufficient for establishing a prognostic indicator of OS. 11 As an emerging field, radiomics has been used to convert qualitative images to quantitative data using a large series of automatically extracted data-characterization algorithms.…”
mentioning
confidence: 99%